Pembelajaran Integratif Berbasis Tauhid bagi Anak Usia Dini Integrative Learning Based on Tauhid for Early Childhood - Naila Fikrina Afrih Lia; Dina Salimatul Khotimah (JURNAL LENTERA ANAK, 2020)
Integrative learning based on Tauhid is one of the lessons that has an important role for early childhood. The attitudes and behavior of children can be seen from the value of their religious and moral development. Observing is the main goal of all activities in life which can be a source of faith for all evil. At the early childhood education level, monotheism is the main foundation in the formation of children’s character so that they can produce superior quality human beings with noble character. This study uses a qualitative descriptive method. Tauhid based PAUD integrative learning can be applied to every child’s activity by applying three values in believing in Allah, namely Tauhid Rubbubiyah, Tauhid Ulluhiyah and Tauhid Asma wa sifat. The purpose of this study was to analyze and describe the tauhid-based PAUD learning program that can shape children’s character from an early age. Cultivate in children a sense of love for the creator, discipline, responsibility and independence for something faced, being honest, respectful and obedient to teachers, parents and caring for others.